Autogenous and total shrinkage of limestone calcined clay cement (LC3) concretes. (3rd January 2022) - Nguyen, Quang Dieu; Afroz, Sumaiya; Zhang, Yingda; Kim, Taehwan; Li, Wengui; Castel, Arnaud
Highlights: The shrinkage development of LC3 concretes was investigated. Higher autogenous shrinkage due to continuous pore structure refinement. Lower drying shrinkage due to finer pore structure. Similar total shrinkage between LC3 and OPC concretes at the later age. Bazant B4 model effectively predicted the developments of total shrinkage. Abstract: In this study, the developments of autogenous and total shrinkage of limestone calcined clay cement (LC3) concretes were investigated. Three concrete grades including 25 MPa, 32 MPa and 45 MPa of both LC3 and general purpose cement (GPC) concretes were considered. Compressive strength and tensile strength were measured until curing of 28 days. In addition, pore size distribution of cementitious pastes was evaluated by using nitrogen adsorption. Several models were used to assess their applicability for LC3 concretes in predicting mechanical properties and shrinkage development. The LC3 concretes showed higher autogenous shrinkage at a later age up to 100 days due to continuous refinement of the pore structure whilst the development of total shrinkage was similar between LC3 and OPC concretes. All models underestimated LC3 concrete autogenous shrinkage and the Bazant B4 model provided the best prediction of total shrinkage development.